Recovery of Cu (II) and Cr (VI) Metals from Electroplating Liquid Waste Using Polymer Inclusion Membrane (PIM) - muhammad cholid djunaidi; Nor Basid Adiwibawa Prasetya; Nur Asih Setyowati; Khabibi Khabibi; Khoirun Nita Ulfia (Dept. of Chemical Engineering, Diponegoro University, 2018)
Research on recovery of Cu (II) and Cr (VI) from electroplating liquid waste has been carried out using a Polymer Inclusion Membrane (PIM). PIM has a high stability to overcome the weakness of liquid membrane instability. The PIM membrane was placed between two phases namely the feed phase as a metal source of Cu (II) from electroplating waste with pH 3 and the receiving phase which is HNO3 solution with pH 1 and pH 4.4 in the feed phase and pH 6.3 in the receiving phase with NaCl 2 N for metal Cr (VI). Recovery efficiency is known by determining the concentration of Cu (II) and Cr (VI) in the feed and receiving phases using AAS, while the membrane characterization were carried out using FTIR, SEM and UV-vis spectroscopy. The resulting PIM membrane has properties of thin, clear and flexible. AAS data showed that the percentage of PIM transport with stirring for 24 hours performed the highest percentage of Cu (II) metal transport from feed phase of 83.41% and transport in the receiving phase of 72.56%. While the percentage of optimum Cr (VI) transport was 97.8% in the feed phase and 76.5% in the receiving phase. The results of membrane characterization using FTIR and UV spectroscopy showed that the PIM membrane was quite stable. While the results of SEM show that there were no pores in the membrane so that the transport occurs by diffusion through the intermediate of the carrier compound. Keywords: electroplating waste; liquid membrane; PIM